A Nonenzymatic Hydrogen Peroxide Electrochemical Sensing and Application in Cancer Diagnosis. Issue 5 (25th January 2021) - Yu, Yan; Peng, Jinrong; Pan, Meng; Ming, Yang; Li, Yan; Yuan, Liping; Liu, Qingya; Han, Ruxia; Hao, Ying; Yang, Yun; Hu, Danrong; Li, He; et al.
Abstract: The diagnosis of malignant tumors is essential for informing clinical decisions regarding therapeutic options. Current imaging and pathological diagnostic methods do not provide quantitative molecular information that is important in tumor identification. Moreover, pathological tissue analysis is dependent on unevenly distributed pathological features. The tumor microenvironment has been documented to have hydrogen peroxide (H2 O2 ). This study presents a biologically sensitive and efficient H2 O2 electrochemical sensor based on PtNi nanoparticle‐doped N‐reduced graphene oxide (PtNi‐N‐rGO) with a low detection limit (2.8 × 10 –9 m ), a fast response time (<6 s) and desirable anti‐interference characteristics. Herein, H2 O2 is used as molecular biomarker. The sensor successfully captures H2 O2 from cancer cells. In addition, it efficiently detects tumor tissues, adjacent tissues, and normal tissues. This study demonstrates the H2 O2 sensor potential to rapidly detect tumor tissues. This technique provides a complementary method for pathological tumor diagnosis that is independent of the traditional pathology labs. Abstract : This study presents a biologically sensitive and efficient H2 O2 electrochemical sensor based on PtNi nanoparticle‐doped N‐reduced graphene oxide (PtNi‐N‐rGO). H2 O2 is used as molecular biomarker. The sensor successfully captures H2 O2 from cancer cells. It efficiently detects tumor tissues, adjacent tissues, and normal tissues. This study demonstrates the H2 O2 sensor potential to rapidly detect tumor tissues. This technique provides a complementary method for pathological tumor diagnosis.